2017
DOI: 10.1038/s41598-017-08686-4
|View full text |Cite
|
Sign up to set email alerts
|

Political Pressures Increased Vulnerability to Climate Hazards for Nomadic Livestock in Inner Mongolia, China

Abstract: Herders in Inner Mongolia experienced two completely different political periods during their last nomadic period between 1961 and 1986. However, climate and technical factors were very similar between these two periods according to statistical analyses. We retrieved historical climate and livestock population data and performed a retrospective study using generalized additive models to analyze three major livestock population demographic metrics changes between these two periods. We found that the sociopoliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Prior studies have revealed that the livestock industry is susceptible to the effects of environmental, social, economic, institutional, and policy factors, which may differ substantially over spatial and temporal scales [10,19,49,50]. In our study, the pastoral population significantly impacted the massive increase in livestock population in Xilinhot in the past 40 years, suggesting a heavy dependence of local pastoralists on the animal husbandry for their livelihoods.…”
Section: Factors Influencing Changes In Livestock Population and Composition During 1970-2010mentioning
confidence: 65%
See 3 more Smart Citations
“…Prior studies have revealed that the livestock industry is susceptible to the effects of environmental, social, economic, institutional, and policy factors, which may differ substantially over spatial and temporal scales [10,19,49,50]. In our study, the pastoral population significantly impacted the massive increase in livestock population in Xilinhot in the past 40 years, suggesting a heavy dependence of local pastoralists on the animal husbandry for their livelihoods.…”
Section: Factors Influencing Changes In Livestock Population and Composition During 1970-2010mentioning
confidence: 65%
“…The snowstorms of 1977 and 1985 [56], as well as the drought during 1999-2001, led to a serious loss for the local animal husbandry, indicating that natural factors, particularly extreme events, were still a major driver for the livestock dynamics in the Xilinhot region. This is also the case in many other arid and semi-arid regions around the world [12,13,19].…”
Section: Factors Influencing Changes In Livestock Population and Composition During 1970-2010mentioning
confidence: 69%
See 2 more Smart Citations